Power Leadership Kepala Ruang Terhadap Motivasi Kerja Perawat Di Ruang Rawat Inap Rumah Sakit Probolinggo - Titik Suhartini (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Good leadership in nursing services will lead to the emergence of quality nurse work motivation and patients get good service. Work motivation will have an effect on generating, directing and maintaining behavior related to the work environment. The purpose of this study was to analyze the relationship between the Head of Room's Power Leadership and Work Motivation of Inpatient Nurses  Methods: The design of this research is correlation research with cross sectional approach. The population in this study were all nurses in the inpatient hospital in Probolinggo Regency, there are 81 people and the number of samples is 68 people. Sampling technique Stratified Random Sampling. Collecting data using a questionnaire then the data is processed using SPSS using the Spearman rank test.Results: The results of the analysis of the leadership power of the head of the room are mostly still moderate, namely 39 people (57.4%) and the motivation of nurses is mostly moderate, namely 35 people (51.5%). The results of the analysis of the leadership of the head of the room with a work motivation of 0.000 (smaller than 0.05) then there is a significant linear relationship between the leadership variable of the head of the room and the work motivation of nurses.Conclusion: The head of the room can always maintain the leadership style that is carried out and always maintain communication with nurses so that good communication is always established and can continue to maintain nurses' work motivation.